ASSESSING AND MITIGATING NOISE POLLUTION IN ACADEMIC ENVIRONMENT AT THE AIR FORCE INSTITUTE OF TECHNOLOGY - Akusu, Patrick O.; Yakubu, Bashir M.; Bello, Yusuf A.; Bashir, Hassan M. (FUDMA JOURNAL OF SCIENCES, 2025)
This study examines the impact of noise pollution within the Faculty of Sciences complex at the Air Force Institute of Technology (AFIT), a relatively young institution within military facility requiring necessary guidelines for safe living. The notable noise generators in this area are power generators and a concrete mixer. This research reveals that noise levels from the identified sources decrease with distance. The maximum sound level of 97 dB, 130 dB, 100 dB, 100 dB, and 150 dB was recorded for 3.5 kVA MAXMECH generator placed on an interlocking floor, 3.5 kVA MAXMECH generator placed on the ground, 4.5 kVA ELEPAQ, 9.5 kVA FIR-MAN, and the concrete mixer respectively. While at 50 m away for the respective machines, the minimum sound level recorded was 49 dB, 39 dB, 38 dB, 35 dB, and 68 dB. Moreover, the safe sound level of 75 dB was attained for the respective machines at a distance of 9 m, 6 m, 12 m, 10 m, and 16 m. Analysis indicates that the generators currently in use are positioned at safe distances from the building, but caution is advised against placing any within the faculty complex due to space constraints. The study underscores the importance of ongoing sound level assessments for all noise-generating equipment. Strategies such as sound absorbers are recommended for noise control. This research contributes valuable insights for maintaining optimal acoustic conditions and promoting a conducive environment for learning and productivity within academic institutions.